Effect of gravity-induced asymmetry on the nonlinear vibration of an overhung rotor - ELIJAH CHIPATO (Communications in Nonlinear Science and Numerical Simulation, 2018)
In this study a mechanical model of an overhung rotor is explored to determine the effect of gravity on the nonlinear dynamics of an aero-engine. The model is an overhung disc with rotor-stator contact. The model has two degrees of freedom with lumped parameters; friction is neglected in the contact and the equations of motion are non-dimensionalised. A parametric study of the non-dimensional gravity parameter is conducted. The bifurcation plots show that gravity plays a crucial role in the nonlinear dynamics of such systems. With zero gravity, as explored in earlier studies, the model has synchronous whirling solutions, and asynchronous partially contacting solutions that are periodic only when viewed in a rotating coordinate system. If the gravity parameter is non-zero, then the dynamics observed are much richer and show additional multi-periodic and chaotic solutions in the stationary frame and continuous contact (full annular rub).